1987
DOI: 10.3928/0098-9134-19870501-04
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness in the Elderly

Abstract: Loneliness has become as much a part of Americana as turkey on Thanksgiving - particularly for older Americans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
4

Year Published

1994
1994
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 21 publications
0
42
0
4
Order By: Relevance
“…Kivett (1979) found that inadequate transportation and unavailability of organized social activity were among the best predictors of loneliness in older adults. Inadequate transportation was also found by Berg, Mellstrom, andPersons (1981, cited in Ryan &Patterson, 1987) to be a correlate of loneliness, presumably because it has implications for the ability to maintain social contacts. Patients with chronic obstructive pulmonary disease and their caregivers have reported heightened feelings of loneliness as a result of the social separation that the disease causes for both (Keele-Card, Foxall, & Barron, 1993).…”
Section: Lack Of Social Network-loss Of Intimatesmentioning
confidence: 81%
See 3 more Smart Citations
“…Kivett (1979) found that inadequate transportation and unavailability of organized social activity were among the best predictors of loneliness in older adults. Inadequate transportation was also found by Berg, Mellstrom, andPersons (1981, cited in Ryan &Patterson, 1987) to be a correlate of loneliness, presumably because it has implications for the ability to maintain social contacts. Patients with chronic obstructive pulmonary disease and their caregivers have reported heightened feelings of loneliness as a result of the social separation that the disease causes for both (Keele-Card, Foxall, & Barron, 1993).…”
Section: Lack Of Social Network-loss Of Intimatesmentioning
confidence: 81%
“…We then turn our focus to depression, which is a major potential consequence of both shyness and loneliness. Like shyness, loneliness does not have a universally accepted defini- [Horowitz, French, & Anderson, 1982;Ryan & Patterson, 1987). Anderson (1992) noted that there is disagreement on whether loneliness should be considered a unidimensional construct (e.g., a simple discrepancy between an individual's desired and obtained social contacts) or a multidimensional construct (e.g., dividing loneliness on distinct and separate dimensions).…”
Section: Consequences Of Shynessmentioning
confidence: 99%
See 2 more Smart Citations
“…Loneliness mayor may not be experienced by the person who is alone and the person who experiences loneliness may or may not be alone (Andersson, 1998 Dugan and Kivett (1994) reported that 21 per cent of rural older Americans experienced 'much loneliness '. Johnson et al (1993) reported that as many as 62 per cent of older people in America experience loneliness, while Ryan and Patterson (1987) found that loneliness was ranked as secondary only to fears about crime and ill-health among older Americans.…”
Section: The Experience and The Prevalence Of Lonelinessmentioning
confidence: 99%